廣義多使用者多天線技術之自動重傳機制及其性能探究 - 伍紹勳; Wu Sau-Hsuan (My University, 2009)
在此研究之中將探討合作式多重存取中繼通訊與中繼廣播通訊之有效通 訊方式，其相對應之多工與多樣性折衷、吞吐量以及與排隊控制之間的交互關 係以作為合作式多用戶通訊系統之設計參考 有鑑於在傳送端擁有所有用戶的通道狀況資訊(CSIT) 對MIMO 廣播通 道的最大可能的總和傳輸率具有決定性之影響。在本計劃的第一年首先將深入 探討並量化通道狀況資訊誤差對MIMO 廣播在快速衰減通道中的總和傳輸率之 影響，並依據此結果設計討論在時變通道中傳送端之前置編碼器以及接收端各 用戶之波束成形器之形式以達成最好之時變MIMO 廣播通道的總和傳輸率。此 部份之結果可視為合作式多用戶通訊系統之性能指標。 接著，在本計劃的第二年將探討多重存取中繼通訊與中繼廣播通訊的多 樣性增益與多工增益折衷(diversity and multiplexing tradeoff, DMT)。有 鑒於多重存取與廣播等多用戶通訊系統中，強大之多重截取干擾會使得系統性 能在有限訊雜比下之行為與其在高訊雜比下之行為有明顯之特徵差異。因此不 同於Zheng and Tse 所提出於高訊雜比下之多工與多樣性折衷的分析方式，本 計畫提案將於有限訊雜比之操作環境下分析合作式多重存取中繼通訊與中繼廣 播通訊之多工與多樣性折衷，以作為合作式多用戶通訊系統之設計參考。 儘管合作式通訊的確可以帶來可觀的通訊容量增益與通訊品質改善，但 是卻也隱含了強制性的重傳機制。在訊雜比相對好以及接收端並無錯誤發生， 並不應該強制性的加入合作式的機制於其中。因此合作式通訊應是當有需要時 才被使用的，以節省合作中繼通訊所需要之額外時間並提高有效之資料吞吐量 (data throughput)。因此在本計劃的第三年將探討合作式中繼通訊與中繼廣播 通訊與自動重傳要求機制(automatic retransmission request, ARQ) 相結合 之最佳方式，相關的資料吞吐量以及與排隊控制、多工與多樣性之間的折衷關 係以發揮合作式多用戶通訊系統之最大效能。

In this research, we will investigate the effective transmission schemes and the corresponding diversity and multiplexing tradeoff (DMT) for the cooperative multiple access relay channel (MARC) and the relay broadcast channel (RBC). The relationship between the throughput, DMT and queuing control will also investigate for automatic retransmission request (ARQ) of MARC and RBC to serve as a design guideline for cooperative multiuser systems. In view of the great impact of the transmitter side channel state information (CSIT) on the sum-rate capacity of multiple input multiple output (MIMO) broadcast channel (BC), the effects of channel estimation errors on the sum-rate capacity of MIMO BC will be investigated in the first year of this project proposal. Based on the analysis, we will further study the appropriate transmit precoder and receive beamformer pair to achieve a better sum-rate capacity of MIMO BC under estimation errors. In the second year of this project proposal, effective approaches and the corresponding DMT analysis will be studied for MARC and RBC. Considering the overwhelming multiple access interference present in multiuser channels, the DMT analysis will be conducted in the finite signal to noise (SNR) regime to better characterize the performance of cooperative MARC and RBC in realistic operation environments. Based on this analysis, we will further study the effective hybrid ARQ and ARQ schemes for MARC and RBC in the third year of this research project. The relationship between the DMT, the data throughput, the queuing control and the maximum transmission delay will be investigated in details to provide an optimal adaptation strategy for cooperative MARC and RBC HARQ protocols.
The Protocols and Performance Analysis for HARQ of Generalize Multiuser Multiple Input Multiple Output Systems